2016
DOI: 10.1016/j.hal.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment of domoic acid exposure: What can be learned from traditional methods and new applications for a technology assisted device

Abstract: Three Tribal Nations in the Pacific Northwest United States comprise the members of the CoASTAL cohort. These populations may be at risk for neurobehavioral impairment, i.e., amnesic shellfish poisoning, from shellfish consumption as a result of repeated, low-level domoic acid (DA) exposure present in local clams. Previous work with this cohort confirmed a high proportion of clam consumers with varying levels of potential exposure over time. Since clams are an episodically consumed food, traditional dietary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Coastal-dwelling tribal nations are at particularly high-risk for long-term, low-dose exposure because of their reliance on the ocean as an essential economic resource, foundation of cultural identity and year-round food source. A dietary survey of tribal members living on three Native American reservations in Washington State found that 84% of respondents indicated recent razor clam consumption (Boushey et al, 2016;Fialkowski et al, 2010). The impact of chronic DA exposure was recently studied in these communities and exposure (as measured by the consumption of razor clams) was associated with decrements in memory that were serious enough to affect everyday living skills (Grattan et al, 2016a(Grattan et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal-dwelling tribal nations are at particularly high-risk for long-term, low-dose exposure because of their reliance on the ocean as an essential economic resource, foundation of cultural identity and year-round food source. A dietary survey of tribal members living on three Native American reservations in Washington State found that 84% of respondents indicated recent razor clam consumption (Boushey et al, 2016;Fialkowski et al, 2010). The impact of chronic DA exposure was recently studied in these communities and exposure (as measured by the consumption of razor clams) was associated with decrements in memory that were serious enough to affect everyday living skills (Grattan et al, 2016a(Grattan et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our model, we also chose to give exposures orally and near the current regulatory limits (Mariën, 1996;Wekell et al, 2004), to bring strong environmental relevance to the study. These results may be particularly significant to already vulnerable communities that have close cultural connections to various types of seafood, such as some coastal Native American Tribes, where up to 84% of people regularly consume razor clams (Boushey et al, 2016). As DA algal blooms continue to increase in frequency and severity around the globe, it is imperative that we continue to advance our understanding of the health consequences associated with chronic, low-level intake of this marine biotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study begun in 2003 determined the incidence and prevalence of domoic acid–related illness among four coastal Tribal communities in the Pacific Northwest. This study has provided a rational basis for shellfish regulation by the tribe and for preventive education to these disproportionately exposed and medically underserved Native American communities ( Boushey et al 2016 ; Roberts et al 2016 ). The educational components relied on TEK to deliver risk messaging and education to the tribes in language that acknowledged the cultural significance of the shellfish and the role that shellfish gathering played in tribal community life ( Tracy et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%